Physics-based modeling and experimental investigation of field-assisted manufacturing processes - Sun, Mingman (Kansas State University, 2022)
This twofold dissertation focuses on physics-based modeling and experimental investigation of field-assisted manufacturing processes. Part I consists of 5 chapters, which investigates ultrafast laser-assisted micro- and nanofabrication by two-photon polymerization. Chapter 1 thoroughly reviews the principle, materials, and applications of two-photon polymerization with the latest developments. Chapter 2 discusses the model development for two-photon polymerization by a Bessel beam. Chapter 3 describes model validation by comparing SEM-measured and model-predicted polymerized pillar structure diameters. Chapter 4 presents a detailed discussion of the simulated results. Chapter 5 states the future research in utilizing the established model as a practical tool to generate the processing science for volumetric additive manufacturing by two-photon polymerization. Part II focuses on ultrasonic-assisted manufacturing for biomass-based products. It has 5 chapters that are separate from those in Part I. The investigation creates a new knowledge base on synchronized torrefaction and pelletizing assisted by ultrasonic vibration to utilize renewable and domestically available biomass. Chapter 1 reviews the composition, structure, and properties of lignocellulosic biomass, and states the conventional biomass preprocessing and pretreatment methods. Chapter 2 presents the experimental platforms for ultrasonic vibration amplitude measurement and synchronized ultrasonic torrefaction and pelleting procedure. Chapter 3 describes a physics-based modeling of synchronized ultrasonic torrefaction and pelleting procedure. Chapter 4 and 5 are conclusions and an outlook for bioenergy research, which are essential when making important strategic and operational decisions in biomass energy manufacturing.
Keywords: Additive manufacturing; Femtosecond laser; Two-photon polymerization; Biomass torrefaction; Ultrasonic; Multiphysics modelling